Выделение формы сигнала в присутствии случайной и регулярной помех; Контроль. Диагностика; № 12 - Авдеева Д. К. Диана Константиновна; Вылегжанин О. Н. Олег Николаевич; Турушев Н. В. Никита Владимирович; Григорьев М. Г. Михаил Георгиевич (2014, 2014)
Заглавие с экрана